2010
DOI: 10.1080/19440040903586299
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and nitrite content in organically cultivated vegetables

Abstract: The nitrate and nitrite content of leaf vegetables (Swiss chard, sea beet, spinach and cabbage), "inflorescence" vegetables (cauliflower) and fruit vegetables (eggplant and vegetable marrow) grown with organic fertilizers have been determined by a modified cadmium–Griess method. Samples were purchased from organic food stores as well as collected directly from an organic farm in Madrid (Spain). Nitrate levels were much higher in the leaf vegetables (especially Swiss chard species; average over the different sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The authors reported a lower nitrate content in organic (from 546 to 1274 mg kg −1 Fw) than mineral fertilized (from 780 to 2113 mg kg −1 Fw) Swiss chard. Matallana González et al [73] in samples of Swiss chard collected directly from an organic farm in Spain found values of nitrate content (2630.4 mg kg −1 Fw) near or higher than the ones purchased from organic food stores (2595 mg kg −1 Fw).…”
Section: Referring To Our Results About Leaf Nomentioning
confidence: 93%
“…The authors reported a lower nitrate content in organic (from 546 to 1274 mg kg −1 Fw) than mineral fertilized (from 780 to 2113 mg kg −1 Fw) Swiss chard. Matallana González et al [73] in samples of Swiss chard collected directly from an organic farm in Spain found values of nitrate content (2630.4 mg kg −1 Fw) near or higher than the ones purchased from organic food stores (2595 mg kg −1 Fw).…”
Section: Referring To Our Results About Leaf Nomentioning
confidence: 93%
“…Alternatively, under the USD 1.9 constraint, a nutritionally adequate solution in rural areas demands the inclusion of wild foods ( Table 4 ). However, their use is limited due to: seasonality, local availability, considerable time consumption for harvest and their content of potentially toxic substances such as nitrates [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we found lower nitrate content in ORG at equal N fertilization levels in both systems. Mineral fertilizer used in CON treatments directly provides nitrate, while compost is slowly decomposable and nitrogen releases gradually [55]. In general, carrot is classified as a vegetable with a low nitrate content, with the average being 200-500 mg kg −1 [56].…”
Section: Discussionmentioning
confidence: 99%